Developing a Local Model to Evaluate the Impact of Information Technology Capabilities on the Performance of Pharmaceutical Firms Using the Mediating Role of Supply Chain Approach (Case Study: Pharmaceutical Firms in Iran) - parvaneh zeraati foulolaei; mehrdad madhoshi; hasanali aghajani; mahmod yahyazadeh far (Journal of Information Technology Management)
In the technology-based industries, such as pharmaceutical industry, the success of the companies depends on their ability to provide new and continuous innovations to the market. The purpose of this study is to investigate the effect of information technology capabilities on the performance of organizations in the pharmaceutical industry in Iran. The research method in this study is survey type and a random sampling method has been used. According to the statistics provided by the Ministry of Health of Iran, there are over 170 active pharmaceutical and chemical companies (chemical and plant) in the country. The population of the study includes all the internal, production, human resources, marketing and sales managers in these 170 companies. They were estimated to be around 746, from which 254 were selected as the sample. The main findings of this research are: 1- The technological capabilities are proved effective on three supply chain approaches of purity, resilience, and agility. 2- Those three supply chain approaches (purity, resilience, and agility) have a positive effect on organizational performance.